Pertumbuhan Sengon dan Produksi Padi Gogo pada Taraf Pemupukan P yang Berbeda dalam Sistem Agroforestri - Derie Kusuma Budi Ningrum; Nurheni Wijayanto; Arum Sekar Wulandari (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Agroforestry of upland rice (Oryza sativa L.) and sengon tree (Paraserianthes falcataria) could increase the growth of sengon trees; however, it would also increase the percentage of empty grain due to shade from the tree. Fertilization with P is expected to increase plant height, grain weight and weight of straw of upland rice and growth of sengon tree. The aim of this research is to analyze the growth and production of sengon and upland rice with agroforestry and P fertilizer application. Application in cultivation of upland rice using split-split plot design. The main plot is agroforestry and monoculture, subplot of Sintanur and Situ Bagendit varieties and split-split plot of P fertilization consisting of 4 levels, namely: P 0 = 0 g / plant, P50 = 3 g / plant, P100 = 6 g / plant and P150 = 9 g / plant. The application of P fertilizer showed that P 100% had high production on Sintanur varieties with monoculture. Agroforestry system can increase the growth of sengon plants.Keywords: agroforestry, P fertilizer, sengon, upland rice.